Supply chain integrated merger and acquisitions (M&As) and firm energy performance - Fengxiang Zhao; Bo Wang; Mei Yu (Chinese Journal of Population, Resources and Environment)
This paper examines the impact of upstream merger and acquisition (M&A) activities driven by supply chain integration motives on firm energy performance. By developing a microlevel theoretical framework, we examine the intricate relationship between firms’ upstream M&A strategies geared toward supply chain integration and their energy efficiency. We examine the impact of upstream M&A activities on energy performance using data from Chinese listed companies from 2007 to 2021. Our findings reveal that upstream M&A initiatives can enhance firms’ energy efficiency, although there are discernible variations in the effects observed for M&A activities targeted downstream or within the same industry. By examining mechanisms, we elucidate the pivotal roles of input substitution effects and productivity enhancements through which upstream M&As boost energy performance. Furthermore, our analysis underscores the catalyzing impact of M&A activities in fostering collaborative innovation in green technologies among firms and suppliers, thus improving productivity and energy efficiency. We provide new microlevel evidence of the relationship between M&A transactions and corporate energy efficiency from upstream and downstream perspectives.